2006
DOI: 10.1111/j.1748-1716.2006.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle type‐specific response of PGC‐1α and oxidative enzymes during voluntary wheel running in mouse skeletal muscle

Abstract: These results suggest that muscle type-specific responses occur during endurance exercise, and that the increase in PGC-1alpha expression is not the only factor that promotes oxidative capacity as a result of endurance exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
37
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 29 publications
(50 reference statements)
10
37
2
Order By: Relevance
“…Interestingly, LC-HF diets seem not to generally affect muscle GLUT4 expression. It is known that especially the anatomic location of the muscle and the type of muscle fiber (including the myosin heavy chain isoform expression profile) plays an important role for GLUT4 expression (15,20,30,32). Our own preliminary data from Western blot experiments using quadriceps muscle samples indicate that GLUT4 expression was not affected by LC-HF diets in that muscle type (data not shown).…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, LC-HF diets seem not to generally affect muscle GLUT4 expression. It is known that especially the anatomic location of the muscle and the type of muscle fiber (including the myosin heavy chain isoform expression profile) plays an important role for GLUT4 expression (15,20,30,32). Our own preliminary data from Western blot experiments using quadriceps muscle samples indicate that GLUT4 expression was not affected by LC-HF diets in that muscle type (data not shown).…”
Section: Discussionmentioning
confidence: 75%
“…PGC-1a expression is downregulated in different models of muscle atrophy, including diabetes, uremia, cancer cachexia, and chronic heart failure [26,27]. In contrast, PGC-1a expression increases in both slow-twitch and fast-twitch muscles following acute exercise and chronic training [45,46]. Therefore, we hypothesized that immobilization would reduce PGC-1a expression in both slow-twitch and fast-twitch muscles.…”
Section: Discussionmentioning
confidence: 94%
“…Numerous studies have demonstrated metabolic substrate and muscle injuries after prolonged endurance exercise (Ikeda et al, 2006;Rezende et al, 2004;Maglara et al, 2003;Shave et al, 2004). In the majority of these studies, however, the control of environmental conditions has been limited during exercise.…”
Section: Discussionmentioning
confidence: 99%